2019
DOI: 10.1088/1361-6528/ab2831
|View full text |Cite
|
Sign up to set email alerts
|

Field-free spin–orbit-torque switching of perpendicular magnetization aided by uniaxial shape anisotropy

Abstract: It has been demonstrated that the switching of perpendicular magnetization can be achieved with spin orbit torque (SOT) at an ultrafast speed and low energy consumption. However, to make the switching deterministic, an undesirable magnetic field or unconventional device geometry is required to break the structure inverse symmetry. Here we propose a novel scheme for SOT-induced field-free deterministic switching of perpendicular magnetization. The proposed scheme can be implemented in a simple magnetic tunnel j… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 68 publications
0
18
0
Order By: Relevance
“…Other manifestations of hybrid ME-SOT heterostructures have been explored to break critical symmetries and lift degeneracies in SOT switching [229][230][231][232]. For instance, SOT switching of a perpendicular magnetic anisotropy (PMA) magnet by the spin Hall effect of isotropic heavy metals is complicated by non-deterministic switching.…”
Section: Hybrid Magnetoelectric-spin-orbit Torque Heterostructuresmentioning
confidence: 99%
“…Other manifestations of hybrid ME-SOT heterostructures have been explored to break critical symmetries and lift degeneracies in SOT switching [229][230][231][232]. For instance, SOT switching of a perpendicular magnetic anisotropy (PMA) magnet by the spin Hall effect of isotropic heavy metals is complicated by non-deterministic switching.…”
Section: Hybrid Magnetoelectric-spin-orbit Torque Heterostructuresmentioning
confidence: 99%
“…When a current crosses the non-magnetic layer, spins are accumulated and a torque switching is generated over the magnetization of the ferromagnetic layer. A faster switching can occur using SOT with the elimination of the time-demanding precessional motion [28]. However, one disadvantage of SOT is that it requires bigger cell size than STT-based applications due to its three terminal structure, so it can be not compatible with high-density applications.…”
Section: Spin-orbit Torque (Sot)mentioning
confidence: 99%
“…Because the spin orbit torque exerted on the electron spin in the FM layer was related to the current density of the NM layer, manipulation of the magnetization direction of the FM layer would be dependent on its position on the NM layer. It has been reported that specific patterning of both FM layer and NM layer could be utilized to control the magnetization state of the FM layer [Safeer 2016, Siddiqui 2020, Martinez 2016, Wang 2019]. Hence, the feasibility of applying such method in spinbased data storage has been confirmed.…”
Section: Introductionmentioning
confidence: 99%